2015
DOI: 10.5978/islsm.15-or-04
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Er, Cr: YSGG laser with ultrasonic preparation on the seal of retrograde cavities

Abstract: Under the conditions of this research, the use of Er, Cr: YSGG laser for retrograde cavity preparation causes significantly less apical leakage and may increase the success rate of endodontic surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In this study, the Er,Cr:YSGG laser preparation of retrovacities did not affect the sealing ability of the MTA; however, caused more leakage through BC-RRM material. Many previous studies have shown the advantages of erbium lasers in periapical surgery, in terms of increased apical sealing [ 6 , 12 , 36 ]. Karlović et al [ 6 ] reported less apical leakage of MTA, Super EBA, and IRM materials in retro cavities prepared by Er:YAG laser, compared to ultrasonic.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the Er,Cr:YSGG laser preparation of retrovacities did not affect the sealing ability of the MTA; however, caused more leakage through BC-RRM material. Many previous studies have shown the advantages of erbium lasers in periapical surgery, in terms of increased apical sealing [ 6 , 12 , 36 ]. Karlović et al [ 6 ] reported less apical leakage of MTA, Super EBA, and IRM materials in retro cavities prepared by Er:YAG laser, compared to ultrasonic.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion was reached due to an explanation that Er,Cr:YSGG laser causes micro-explosions of the water in dentin, resulting in the removal of smear layer, thus allowing retrograde filling material to penetrate into these tubules and decrease microleakage. [ 15 23 ]…”
Section: Discussionmentioning
confidence: 99%